Finite Element Simulation in Superplastic forming of Friction Stir Welded Aluminium Alloy 6061-T6 - Ganesh, P (International Journal of Integrated Engineering, 2011)
Superplasticity in materials is the ability of materials to achieve large elongation only under specific conditions of temperature and strain rate. Superplastic Forming (SPF) is an important industrial process that has found application in sheet metal forming in the aerospace and automotive industries. Friction Stir Welding (FSW) is a solid state joining process that can alter the grain structure of the parent material. FSW process is an effective tool to refine the grain structure of the sheet metal and enhance their Superplasticity. Friction Stir Welding was used to join Superplastic AA 6061-T6 sheets. The Finite Element Simulation was performed for the Superplastic Forming of the Friction Stir Welded joints to evaluate the thinning and formability of AA 6061-T6 for hemispherical shape. The commercially available Finite Element Software ABAQUS was used to execute these simulations.